Genetic analyses suggest no immigration of adult females and their offspring into the Sonso community of chimpanzees in the Budongo Forest Reserve, Uganda - Langergraber, Kevin E.; Rowney, Carolyn; Crockford, Catherine; Wittig, Roman; Zuberbühler, Klaus; Vigilant, Linda (My University, 2014)
Chimpanzees are frequently used to illustrate the relationship between sex differences in dispersal and sex differences in cooperation in primates and other group-living mammals. Male chimpanzees are highly philopatric, typically remaining in their natal communities for their entire lives to cooperate with related males in competition against less related males from other groups, whereas females typically disperse once at adolescence and cooperate with each other less frequently. However, there have been a few reports of dependent male offspring joining groups when their mothers transferred between communities as adults. Although such events are difficult to document, determining how often they actually occur is important for elucidating the links between philopatry, kinship, and cooperation in both chimpanzees and group-living animals more generally. Here we use genetic analyses to investigate a previous report of a large-scale transfer of many females and their offspring into the Sonso community of chimpanzees in the Budongo Forest Reserve, Uganda. Using autosomal microsatellite genotypes, we assigned a Sonso father to ten of the fourteen putative immigrants, and found that the four putative immigrants for whom we could not assign a Sonso father (perhaps due to incomplete sampling of all Sonso candidate fathers) nevertheless had Y-chromosome microsatellite haplotypes that were common in Sonso males but absent in males from four other chimpanzee communities at Budongo. These results suggest that these putative immigrant females and their offspring were probably actually long-term residents of Sonso whose identifications were delayed by their peripheral or unhabituated status. These results are consistent with other genetic and behavioral evidence showing that male between-community gene flow is exceedingly rare in east African chimpanzees. Am. J. Primatol. 76:640-648, 2014. (c) 2014 Wiley Periodicals, Inc.